Case report of severe myocarditis in an immunocompromised child with Respiratory Syncytial Virus infection - Hiroki Miura; Fumihiko Hattori; Hidetoshi Uchida; Tadayoshi Hata; Kazuko Kudo; Masatoki Sato; Tetsushi Yoshikawa (BMC, 2018)
Abstract Background Respiratory syncytial virus (RSV) infection is common and may be severe among patients with preexisting cardiac anomalies, but direct involvement of myocardial damage is not common in those patients. Additionally, myocardial involvement has been rarely described among immune compromised children. Case presentation A 4-year-old girl with acute lymphoblastic leukemia who received maintenance chemotherapy in an outpatient clinic developed systemic inflammatory response syndrome. RSV infection was confirmed by a positive rapid antigen test and serological assay. Subsequently, she was diagnosed with severe myocarditis caused by RSV infection, which was diagnosed by abnormal findings of cardiac echography and ECG and elevated biomarkers for myocardial damage. Then, she was treated in the intensive care unit for 13 days. High amounts of RSV type B RNA was detected in tracheal aspirates and serum sample. Conclusion This case report emphasizes that RSV infection may be associated with myocarditis in immunocompromised children receiving maintenance chemotherapy.